Transforming Tofu Waste into a Growth Medium: Boosting Biomass and Proximate Content of Microalgae - Nita Ariestiana Putri; Resti Nurmala Dewi; Rizka Ayu Yuniar; Ranti Amanda Mauliasantri (International Journal of Marine Engineering Innovation and Research, 2024)
This study explores the potential of tofu waste as a cost-effective alternative growth medium for cultivating Spirulina sp. and Nannochloropsis oculata, addressing the high costs of traditional nutrient media that limit large-scale applications. Despite the nutrient richness of tofu waste, its use as a sustainable growth substrate remains underexplored. This research aims to fill this gap by evaluating the growth performance and nutritional suitability of these microalgae in tofu-based media compared to standard controls. The cultivation process was conducted in a closed photobioreactor system, with harvesting methods including flocculation, centrifugation, and filtration. Results showed that tofu waste media supported biomass production comparable to standard cultivation media, with the highest biomass concentrations recorded at the 20% tofu waste treatment, yielding 0.23 ± 0.05 g L-1 for Spirulina sp. and 0.53 ± 0.2 g L-1 for Nannochloropsis oculata. At this concentration, the final COD levels were 840.84 mg L-1and 825.90 mg L-1, respectively. The lipid and protein contents were 2.44% and 1.71% for Spirulina sp., and 1.21% and 1.50% for Nannochloropsis oculata, respectively. These findings demonstrate that tofu waste can serve as an effective and low-cost growth substrate for Spirulina sp. and Nannochloropsis oculata, promoting circular economy principles within many sectors such as energy, food, and agriculture. This study underscores the potential of waste utilization to enhance the sustainability and economic viability of microalgae cultivation.